PENGHINDARAN PAJAK DI INDONESIA: PROFITABILITAS, LEVERAGE, CAPITAL INTENSITY - Puspitasari, Dhestiara; Radita, Ferensia; Firmansyah, Amrie (JURNAL RISET AKUNTANSI TIRTAYASA, 2021)
This study examines the effect of profitability, leverage, and capital intensity on tax avoidance in Indonesia. The method used in this research is the quantitative method. The sample used in this research is mining sector companies listed on the Indonesia Stock Exchange (IDX) from 2016 to 2019. This study employed a purposive sampling technique, a sample of 72 observations. Hypothesis testing is performed using multiple linear regression analysis with panel data. This study indicates that profitability is positively associated with tax avoidance, the capital intensity is negatively associated with tax avoidance. However, leverage is not associated with tax avoidance. This study indicates that the Indonesian Tax Authority should pay attention to its net income and fixed asset as part of the information to enhance the policy.